The Effect of Broker–Borrower Interaction on Mortgage Defaults - Caroline Faustina Wicaksono; Njo Anastasia (Petra International Journal of Business Studies, 2023)
This research proxy uses the distance between brokers and borrowers to explore the interaction between brokers who provide consulting services to prospective property buyers. Meanwhile, the view from the banking side is assessing the risk profile of prospective mortgage borrowers. The research data collection is information on mortgage borrowers from Private Banks in Surabaya branches from the period 2015 - 2020 who used the help of real estate agents when buying a house and collected 1295 transactions. Data processing using probit regression. The test results show that the interaction between brokers and borrowers using distance as a proxy has no significant impact on mortgage defaults. Borrower interest rates raised by the company showed a substantial negative relationship with mortgage default. The study also reveals that borrower income has no impact on mortgage default. The managerial implication for banks is to determine the strategy of cooperation with property brokers to increase mortgage funding.